2019
DOI: 10.1039/c9sc02520k
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of small-molecule inhibitors targeting the ribosomal peptidyl transferase center (PTC) of M. tuberculosis

Abstract: A fast, accurate, and cost-effective design of small-molecule inhibitors that target RNA using a combined NMR-fragment-based and virtual screening.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Tam et al: Discovery of small-molecule inhibitors targeting the ribosomal peptidyl transferase center (PTC) of M. tuberculosis. [16] Fluorescence-based competition assay…”
Section: Lee Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Tam et al: Discovery of small-molecule inhibitors targeting the ribosomal peptidyl transferase center (PTC) of M. tuberculosis. [16] Fluorescence-based competition assay…”
Section: Lee Et Almentioning
confidence: 99%
“…the ribosomal peptidyl transferase center (PTC) of M. tuberculosis. [16] Tanida et al: Alchemical free energy calculations via metadynamics: Application to the theophylline-RNA aptamer complex. [22] Differential scanning fluorimetry (DSF) (future perspective)…”
Section: Tam Et Al: Discovery Of Small-molecule Inhibitors Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning has been applied to a docking-based approach targeting the ribosomal peptidyl transferase centre (PTC) of M. tuberculosis [67] . This study provided validation for machine learning to be applied for drug discovery, as the generated model predicted binding efficiency to the PTC which matched experimental results [67] . The model was trained using the pose outputs from molecular docking, focussing on the eleven-atom core structure of all the phenylthiazole compounds screened.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…The starting point for the drug discovery study reported here is our previous work on the development of small-molecule inhibitors that target the ribosomal peptidyl transferase center (PTC) of Mycobacterium tuberculosis , the bacterium causing tuberculosis. The PTC of the M. tuberculosis ribosome is an important hub for protein synthesis and is hence an effective clinical target [ 9 ] (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%